Validation of a survey methodology for gastroesophageal reflux disease in China - Cao, Yang (BioMed Central, 2008)
BACKGROUND: Gastroesophageal reflux disease (GERD) causes a wide range of clinical symptoms and potentially serious complications, but epidemiological data about GERD in China are limited. The aim of this pilot study was to develop and validate a methodology for the epidemiological study of GERD in China. METHODS: Regionally stratified, randomized samples of Shanghai residents (n = 919) completed Mandarin translations of the Reflux Disease Questionnaire (RDQ), GERD Impact Scale, Quality of Life in Reflux and Dyspepsia (QOLRAD) questionnaire and 36-item Short Form Health Survey (SF-36). Reliability and construct validity were tested by appropriate statistical analyses. RESULTS: The response rate was 86%. The test-retest reliability coefficients for the RDQ, GERD Impact Scale, QOLRAD and SF-36 were 0.80, 0.71, 0.93 and 0.96, respectively, and Cronbach's alpha coefficients were 0.86, 0.80, 0.98 and 0.90, respectively. Dimension scores were highly correlated with the total scores for the QOLRAD and SF-36, and factor analysis showed credible construct validity for the RDQ, GERD Impact Scale and SF-36. The RDQ GERD score was significantly negatively correlated with QOLRAD dimensions of food and drink problems and social functioning, and was significantly negatively correlated with all dimensions of the SF-36. All eight of the SF-36 dimensions were significantly correlated with the QOLRAD total score. CONCLUSION: This study developed and tested a successful survey methodology for the investigation of GERD in China. The questionnaires used demonstrated credible reliability and construct validity, supporting their use in larger epidemiological surveys of GERD in China.